2019
DOI: 10.1042/bsr20190415
|View full text |Cite
|
Sign up to set email alerts
|

EBV encoded miRNA BART8-3p promotes radioresistance in nasopharyngeal carcinoma by regulating ATM/ATR signaling pathway

Abstract: Resistance to radiotherapy is one of the main causes of treatment failure in patients with nasopharyngeal carcinoma (NPC). Epstein-Barr virus (EBV) infection is an important factor in the pathogenesis of NPC, and EBV-encoded microRNAs (miRNAs) promote NPC progression. However, the role of EBV-encoded miRNAs in the radiosensitivity of NPC remains unclear. Here, we investigated the effects of EBV-miR-BART8-3p on radiotherapy resistance in NPC cells in vitro and in vivo, and explored the underlying molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Treatment with KU60019 or AZD6738 increases the radiosensitivity of NPC by suppressing the expression of p-ATM and p-ATR, indicating that EBV-miR-BART8-3p promoted radioresistance in NPC by modulating the activity of the ATM/ATR signaling pathway. 282 …”
Section: Non-coding Rna (Ncrna) and Ebv-associated Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with KU60019 or AZD6738 increases the radiosensitivity of NPC by suppressing the expression of p-ATM and p-ATR, indicating that EBV-miR-BART8-3p promoted radioresistance in NPC by modulating the activity of the ATM/ATR signaling pathway. 282 …”
Section: Non-coding Rna (Ncrna) and Ebv-associated Tumorsmentioning
confidence: 99%
“…Treatment with KU60019 or AZD6738 increases the radiosensitivity of NPC by suppressing the expression of p-ATM and p-ATR, indicating that EBV-miR-BART8-3p promoted radioresistance in NPC by modulating the activity of the ATM/ATR signaling pathway. 282 EBV-miR-BART13-3p. Vesicle-bound EBV-miR-BART13-3p in circulation distinguished NPC from other head and neck cancers and asymptomatic EBV-infections.…”
Section: Non-coding Rna (Ncrna) and Ebv-associated Tumorsmentioning
confidence: 99%
“…Studies have shown that 52 % of NPC demonstrated high level expression of EBV-miR-BART8-3p and could induce EMT, promoting the metastasis of cells [17], which was consistent with our results. In our previously reported study, we found that the EBV-encoded miRNA BART8-3p promoted radioresistance in nasopharyngeal carcinoma by regulating the ATM/ATR signaling pathway [18]. In this study, we combined radioresistance with metastasis and found that radioresistant NPC cells were characterized by the overexpression of miR-BART8-3p , promoting PAG1-dependent EMT and metastasis.…”
Section: Discussionmentioning
confidence: 64%
“…There are also reports that miR-BART2-5p can be used as an early detection indicator for patients with nasopharyngeal carcinoma [16]. Experiments have shown that miR-BART8-3p can regulate ataxia telangiectasia mutations / ataxia telangiectasia mutations and Rad3 (ATM / ATR) The activity of related signaling pathways promotes NPC's radiation resistance [17]. MiR-BART15 is capable of targeting nucleotide-bound oligomerization domain-like receptor family pyridine domaincontaining 3 (NLRP3) with less in ammation to limit in ammation and promote EBV infection [18].…”
Section: Discussionmentioning
confidence: 99%